The system of kinship and family - marriage relations of the kazakh (by the materials of the Pavlodar region) (Journal of history, 2023)
In the article, the author examines the features of the system of kinship and family-marriage relations of the Kazakhs of the Pavlodar region based on the materials of ethnographic expeditions to the Akkol-Zhaiylma region. Here, in 2004-2015, complex ethnographic and archaeological studies were carried out, material was collected about ethno-transformational processes in the modern Kazakh village, about their consequences. Sacred Akkol (Akkol-Zhaiylma) is a fertile land located in the central part of Saryarka. This region, unique in ethnographic and archaeological terms, is located between the Shiderti and Olenti rivers. Since ancient times, it has been one of the important centers of the Great Steppe. Some information about this region can be found in ancient and medieval genealogical and historical records. Having studied them, we realized that Akkol-Zhaiylma occupies no less place in Kazakh history than such historical centers as Bayanaul, Karkaraly, Ulytau.The purpose of the study is to identify the features of the system of kinship and family and marriage relations of local Kazakhs based on the collected field materials. For this, ethnological research methods were used, including observation, conversation, and analysis. The study was conducted in the field of family and marriage ethnology. We realized that traditional family relations in this region are combined with the innovations of the time. Many traditions are preserved. The first results of the study can be used in determining the state family and demographic policy, that is, they are suitable for developing methodological recommendations for the relevant institutions.Key words: kinship system, family and marriage relations, ethnocultural processes, Pavlodar region, Akkol-Zhaiylma, traditions, field ethnography.